Terpaan Iklan Digital, Word Of Mouth dan Komunikasi Pemasaran Interaktif pada Keputusan Pembelian Produk Perawatan Tubuh - Paramita Purnama; Rosita Anggraini; Arintowati Hartono; Irwansyah; Niken F. Ernungtyas (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
Media Social Instagram turn marketing communication into interactive. On theother hand conventional approaches such as word of mouth are still used to drivepurchasing decisions. The study discusses four main concepts namely exposure toadvertising on social media, word of mouth, and interactive marketing communication asindependent variables. While the purchase decision as the dependent variable. The articleaims to describe the influence between advertising exposure, word of mouth andinteractive marketing communication on purchasing decisions in the context of body careproducts and services. This study collects data through online surveys. Respondents (n =100) come from Instagram account followers @thecliniccipete and are chosen based onmembership or have made a previous purchase. Data analysis used univariate analysisfor demographic data and bivariate analysis for variables. Bivariate analysis uses simple linear regression to test three hypotheses. The result of regression test shows thatstatistically all hypotheses have an influence on purchasing decisions with different levelsof influence strength. Ad exposure and word of mouth variables show a strong influenceon purchasing decisions. However, interactive marketing communication shows amoderate influence on purchasing decisions. Based on the three hypotheses known wordof mouth is the most powerful variable that explains purchasing decisions in the contextof body care products and services.